THE IMPACT OF COOPERATIVE LEARNING TYPE MAKE A MATCH TEACHING MODEL TOWARD UNDERSTANDING SAINS CONCEPT IN THE REVIEW OF LEARNING MOTIVATION IN ELEMENTARY SCHOOL - Istabiqul Ilma; Kartono Kartono; Anesa Surya (Universitas Sebelas Maret, 2018)
The low of understanding sains concept and learning motivation caused by implementation of the teaching model that not appropiete. One of the learning model that impact to understanding sains concept and learning motivation was cooperative learning type make a match. The purposes of the research are to know (1)the difference of understanding sains concept between students that teached by cooperative learning type make a match model and students that teached by explicit instruction model; (2) the difference of understanding sains concept between students that had high learning motivation and students that had low learning motivation. The research was used Quasi Eksperimental method with 2x2 factorial design. This research used Two Ways Anava data analysis. The conclution were (1) there was the difference of understanding sains concept between students that teached by cooperative learning type make a match model and students that teached by explicit instruction model; (2) there was the difference of understanding sains concept between students that had high learning motivation and students that had low learning motivation.